Reflections on Angola's 1992 Election: A Photo Essay - Gastrow, Claudia (Kronos: Southern African Histories, 2019)
In October 1992, Angola experienced its first democratic election. Although independence had been achieved in 1975, the rivalries between independence movements and the geo-political interests of the Cold War, led to an immediate plunge into civil war between the MPLA (Popular Movement for the Liberation of Angola), the FNLA (National Front for the Liberation of Angola) and UNITA (National Union for the Total Independence of Angola). By the end of the 1970s, the FNLA, originally backed by Mobutu’s Zaire and the USA, had become a spent force. However, the MPLA and UNITA continued to wage war, the former backed by international socialist forces and the latter by South Africa and covertly the United States. Angola’s war thus became a microcosm, not only of the domestic tensions wrought by centuries of Portuguese colonial actions, but of the developing Cold War and the regional effects of apartheid militarism across southern Africa. With the gradual decline of the Soviet Union, the faltering of apartheid in South Africa as talks began with the ANC, and an acknowledged military stalemate reached with the defeat of South African troops at the battle of Cuito Cuanavale, negotiations ensued for the mutual withdrawal of Cuban and South African troops from the country. These were followed by the Bicesse Peace Accords signed by UNITA and the MPLA in which, among other things, the two factions agreed to end hostilities and hold elections.